ENHANCING LEGAL OVERSIGHT FOR THE MANAGEMENT OF OLD OIL WELLS IN NORTH ACEH REGENCY, INDONESIA - Arif Rahman; Jamaluddin Jamaluddin; Elidar Sari; Faisal Faisal; Nurdin Nurdin; Dilshad Shaik (Kanun Jurnal Ilmu Hukum, 2023)
The control and exploitation of aging oil and gas wells in North Aceh Regency present intricate challenges and conflicts. This article sheds light on the various conflicts arising from this issue and propose potential solutions for their resolution. This article adopts a normative legal research approach, complemented by in-depth interviews, to examine the legal dimensions of control and exploitation by local communities. The findings highlight the necessity of clear regulations in the management of old oil wells to prevent illegal drilling or unauthorized tapping. Specifically, the government should establish robust regulations concerning the mechanism for transferring old oil wells left by companies. In this context, corporations can involve local residents who engage in activities to rejuvenate the wells. While local communities rely on customary law for control and exploitation of old oil wells, the government's approach is based on statutory regulations. By addressing these legal aspects and promoting collaboration between stakeholders, a more effective and harmonious management of aging oil and gas wells can be achieved in North Aceh Regency.